THE INFLUENCE OF DOMESTIC INVESTMENT AND FOREIGN INVESTMENT ON ECONOMIC GROWTH IN NORTH SUMATRA PROVINCE IN 2001-2020 - Zahra, Dwi Atika; Irawan, Fais; Almas, Khairunnisa Umi; Sihotang, Sabrina Erisa Aulia; Mardiah, Siti; Batu, Siska Lumban; Sianturi , Rejosu Vanhot (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2024)
Domestic Investment (PMDN) and Foreign Investment (PMA) have an influence on economic growth, this study aims to analyze the extent of the influence between PMDN and PMA on economic growth in North Sumatra. The data in this study are secondary data from the Statistics Indonesia of North Sumatra Province with a period of 20 years (2001-2020). The approach used is quantitative, and multiple regression analysis to identify the relationship between PMDN, PMA, and GRDP variables. The results of the study indicate that both PMDN and PMA have a significant positive influence, both partially and simultaneously, on economic growth in North Sumatra. The results of the inferential analysis show that the PDMN variable has a calculated t value of 3.964> t table 1.73961, with a significant level of t of (0.01 <0.05) so there is a positive and significant influence of PDMN Use on Economic Growth. The PMA variable has a calculated t value of 4.366 > t table of 1.73961 showing that it has a positive and significant influence between PMA on Economic Growth. There is a significant positive relationship between PMDN and PMA in producing synergy that is very important for economic growth. The calculated f test of 39.118 > f table of 3.59 shows that the proposed hypothesis is proven true. The results show the importance of government efforts in creating a conducive investment climate through supportive policies, as well as relevant infrastructure improvements. Synergy between the government, investors, and local communities is very important to ensure that economic benefits can be felt evenly.